PEMBERDAYAAN EKONOMI IBU-IBU MELALUI PELATIHAN PEMBUATAN DODOL DI KELURAHAN WARURUMA KOTA BAUBAU - Uli, Nur Zarliani; Agustyawati, Dwi; Pardana, Deki; Rusdin, Rusdin (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service activity aims to empower housewives in Waruruma Village through training in dodol production based on local resources, such as coconut and brown sugar. The activity includes initial surveys, socialization, technical production training, marketing strategies, and business assistance. The results of the activity demonstrate an improvement in participants' skills, the formation of small business groups, and the emergence of initial social and economic impacts, such as product orders and increased self-confidence. The activity also promotes collaboration among participants and fosters an entrepreneurial spirit based on local resources. Despite some challenges, such as limited production tools and unresolved legal aspects of the products, the training has proven effective in enhancing household economic capacity. To expand the impact of the activity, sustained support from the government, higher education institutions, and business partners is needed to strengthen community economic empowerment in a self-reliant and sustainable manner.